2019
DOI: 10.1107/s1600576719013955
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of amorphous siliceous fly ash in hydrated blended cement pastes by X-ray powder diffraction

Abstract: X‐ray powder diffraction (XRPD)‐based quantitative phase analysis is a common technique for studying the hydration of cementitious systems. Hydrated cements often comprise several amorphous or nanocrystalline phases. This paper presents a protocol for the quantification of amorphous siliceous fly ash in hydrated cement using XRPD based on the Rietveld PONKCS (partial or no known crystal structure) method. The protocol is validated by comparison against independent measurements, such as Ca(OH)2 content by therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Based on this method, the scale factor, virtual Miller constant, and corresponding intensity of silica fume were probabilistically calculated to generate the hypothetical space group for the diffraction pattern of silica fume, and a similar method was used to generate the C-S-H pattern. The XRD pattern obtained from the OPC cured for 7 years was used after excluding peak contributions from the known crystalline phases [ 36 ]. Then, the fitted patterns of the silica fume and C-S-H were used for the quantitative phase analysis of the UHPC to evaluate the weight variation of the two amorphous phases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this method, the scale factor, virtual Miller constant, and corresponding intensity of silica fume were probabilistically calculated to generate the hypothetical space group for the diffraction pattern of silica fume, and a similar method was used to generate the C-S-H pattern. The XRD pattern obtained from the OPC cured for 7 years was used after excluding peak contributions from the known crystalline phases [ 36 ]. Then, the fitted patterns of the silica fume and C-S-H were used for the quantitative phase analysis of the UHPC to evaluate the weight variation of the two amorphous phases.…”
Section: Resultsmentioning
confidence: 99%
“…For the PONKCS method and subsequent refinement processes, the background was excluded by using a polynomial function of an order less than 5. Previous studies indicated that inaccurate fitting may occur when a low angle range is included in the PONKCS method or Rietveld analysis [ 36 ]. In the present study, the refinement was performed from 8˚ 2θ degrees, considering the presence of ettringite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would require either the use of a high-order polynomial or a high starting angle. For example, Li et al [109] quantified the presence of fly ash in hydrated pastes using powder and slice samples. The authors observed strong low-angle scattering, so the best XRD pattern fitting was obtained for the starting angle of 13.5° 2θ (CuKα).…”
Section: Background Fitmentioning
confidence: 99%
“…The fact that the amorphous/nanocrystalline structure of C-(A)-S-H yields a diffuse scattering signal in XRD is well known in the literature, and different approaches were used to describe its contribution in powder, slice, and fresh samples. Snellings and co-authors [103,109] created a C-S-H model based on a set of four pseudo-Voigt (PV) peaks obtained from a seven-year-old hydrated white cement paste. Bergold et al [24] created a hkl phase using a Pawley range to fit a fully-hydrated C3S sample (containing only portlandite and C-S-H) with the crystal structure of 14 Å tobermorite (F2dd space group) from [112] as a starting point, obtaining the refined lattice parameters a = 11.81906 Å; b = 7.07097 Å; c = 58.92196 Å.…”
Section: C-(a)-s-hmentioning
confidence: 99%